Determinants of severity levels of anemia among pregnant women in Sub-Saharan Africa: multilevel analysis - Tirore, Lire Lemma; Areba, Abriham Shiferaw; Tamrat, Habtamu; Habte, Aklilu; Abame, Desta Erkalo (Frontiers in Global Women's Health, 2024)
Background: Anemia is a severe public health problem affecting 54% of pregnant women in SSA Yet, only a limited number of studies have provided a partial assessment of the pooled prevalence and related determinants of the severity levels of anemia in pregnant women in SSA. Therefore, this study provides the most recent estimates of anemia severity levels and related determinants.The most recent Demographic Health Survey (DHS) dataset of 21 sub-Saharan African countries which were collected between 2015 and 2022 were used. A total of 14098 pregnant women were included. Multilevel ordinal logistic regression was used.The pooled prevalence of anemia was 51.26%. Pregnant women who were in the old age groups, and who have attended secondary and higher education were less likely to be at higher levels of anemia. Those women who have given birth to >1 children in the last 5 years, pregnant women in second and third trimester and living in poorest households had greater odds of being at higher levels of anemiaIn Sub-Saharan Africa, anemia is a severe public health concern for pregnant mothers. When developing and implementing strategies for the prevention and control of anemia, it is imperative to take into account the individual and community circumstances. Programs for the prevention and control of anemia should incorporate the economic and educational empowerment of women.